Mammal hyaluronidase activity on chondroitin sulfate and dermatan sulfate: Mass spectrometry analysis of oligosaccharide products. (12th January 2021) - Bilong, Mélanie; Bayat, Parisa; Bourderioux, Matthieu; Jérôme, Murielle; Giuliani, Alexandre; Daniel, Régis
Abstract: Mammalian hyaluronidases are endo- N -acetyl-D-hexosaminidases involved in the catabolism of hyaluronic acid (HA) but their role in the catabolism of chondroitin sulfate (CS) is also examined. HA and CS are glycosaminoglycans implicated in several physiological and pathological processes, and understanding their metabolism is of significant importance. Data have been previously reported on the degradation of CS under the action of hyaluronidase, yet a detailed structural investigation of CS depolymerization products remains necessary to improve our knowledge of the CS depolymerizing activity of hyaluronidase. For that purpose, the fine structural characterization of CS oligosaccharides formed upon the enzymatic depolymerization of various CS subtypes by hyaluronidase has been carried out by high-resolution Orbitrap mass spectrometry (MS) and extreme UV (XUV) photodissociation tandem MS. The exact mass measurements show the formation of wide size range of even oligosaccharides upon digestion of CS-A and CS-C comprising hexa- and octa-saccharides among the main digestion products, as well as formation of small quantities of odd-numbered oligosaccharides, while no hyaluronidase activity was detected on CS-B. In addition, slight differences have been observed in the distribution of oligosaccharides in the digestion mixture of CS-A and CS-C, the contribution of longer oligosaccharides being significantly higher for CS-C. The sequence of CS oligosaccharide products determined XUV photodissociation experiments verifies the selective β(1 → 4) glycosidic bond cleavage catalyzed by mammal hyaluronidase. The ability of the mammal hyaluronidase to produce hexa- and higher oligosaccharides supports its role in the catabolism of CS anchored to membrane proteoglycans and in extra-cellular matrix.